2017
DOI: 10.1186/s12870-017-0998-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis of defense mechanisms in upland tetraploid switchgrass to greenbugs

Abstract: BackgroundAphid infestation of switchgrass (Panicum virgatum) has the potential to reduce yields and biomass quality. Although switchgrass-greenbug (Schizaphis graminum; GB) interactions have been studied at the whole plant level, little information is available on plant defense responses at the molecular level.ResultsThe global transcriptomic response of switchgrass cv Summer to GB was monitored by RNA-Seq in infested and control (uninfested) plants harvested at 5, 10, and 15 days after infestation (DAI). Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
61
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 123 publications
(145 reference statements)
10
61
0
Order By: Relevance
“…3a, b and c ). The up-regulation of genes involved in oxidative-reduction process has been reported in several plants in response to herbivory, such as in barly in response to Diuraphis noxia Kurdjumov (Hemiptera: Aphididae) [ 47 ], in switchgrass exposed to greenbug [ 48 ], in soybean at both compatible and incompatible interactions with soybean aphid [ 37 , 49 ], and in cotton in response to Bemisia tabaci Gennadius (Hemiptera: Aleyrodidae) [ 46 ]. Our outcomes corroborate these studies and suggest that oxidative responses that are elicited in the resistant genotype are may be the key components of sorghum resistance to sugarcane aphids.…”
Section: Resultsmentioning
confidence: 99%
“…3a, b and c ). The up-regulation of genes involved in oxidative-reduction process has been reported in several plants in response to herbivory, such as in barly in response to Diuraphis noxia Kurdjumov (Hemiptera: Aphididae) [ 47 ], in switchgrass exposed to greenbug [ 48 ], in soybean at both compatible and incompatible interactions with soybean aphid [ 37 , 49 ], and in cotton in response to Bemisia tabaci Gennadius (Hemiptera: Aleyrodidae) [ 46 ]. Our outcomes corroborate these studies and suggest that oxidative responses that are elicited in the resistant genotype are may be the key components of sorghum resistance to sugarcane aphids.…”
Section: Resultsmentioning
confidence: 99%
“…Egg deposition on leaves also induced Pip accumulation and systemic resistance dependent on both ALD1 and FMO1 (Hilfiker et al ., ), indicating that NHP functions as an inducer for this insect egg‐triggered systemic plant response. Marked accumulation of Pip also occurred in aphid‐infested soybean and switchgrass ( Panicum virgatum ) leaves, pointing to a possible role for the Pip/NHP pathway in plant–aphid interactions (Klein et al ., ; Donze‐Reiner et al ., ). In addition, roots of the model legume Lotus japonicus infected with the symbiotic rhizobium Mesorhizobium loti exhibited enhanced expression of the L. japonicus ALD1 ( LjALD1 ) gene, and silencing of LjALD1 by RNAi resulted in a reduction of the size of developing nodules (Chen et al ., ), consistent with a potential influence of Pip on nodule formation.…”
Section: Potential Involvement Of the Nhp Pathway In Other Biologicalmentioning
confidence: 97%
“…Previous studies have demonstrated that S. graminum feeding induced SA-and JA-dependent defence pathways in sorghum (Sorghum bicolor) [28], and reactive oxygen species (ROS) levels, peroxidase (POD) and laccase activities were also increased in switchgrass (Panicum virgatum) after S. graminum feeding [29]. However, few studies have been conducted to identify the defence mechanisms in wheat in response to S. graminum feeding, and the mechanisms underlying the induction of damage by S. graminum infestation are still unclear.…”
mentioning
confidence: 99%